Dataset DrivAer hp-F: Force Measurements in Yaw Conditions - Rijns, Steven; Teschner, Tom-Robin; Blackburn, Kim; Ramos Proenca, Anderson; Brighton, James (Cranfield University, 2024)
Dataset for the aerodynamic force measurements conducted on the 35% scale DrivAer hp-F model at various yaw angles in the 8x6 wind Tunnel at Cranfield University. The dataset includes aerodynamic force coefficients results from measurement on the following vehicle configurations: - DrivAer hp-F standard configuration (no spoiler or rear wing) - DrivAer hp-F spoiler configuration - DrivAer hp-F rear wing configuration The measurements on the DrivAer hp-F rear wing configuration have been conducted three times for repeability. In reference to the publication: Steven Rijns, Tom-Robin Teschner, Kim Blackburn, Anderson Ramos Proenca, James Brighton; Experimental and numerical investigation of the aerodynamic characteristics of high-performance vehicle configurations under yaw conditions. Physics of Fluids 1 April 2024; 36 (4): 045112. https://doi.org/10.1063/5.0196979 CAD files for the DrivAer hp-F configurations are available at: Rijns, Steven; Teschner, Tom-Robin; Blackburn, Kim; Ramos Proenca, Anderson; Brighton, James (2024). DrivAer hp-F: Spoiler & Rear Wing Configurations Geometry Pack. Cranfield Online Research Data (CORD). Dataset. https://doi.org/10.17862/cranfield.rd.25715202
Keywords: DrivAer'; 'Aerodynamics'; 'Wind Tunnel'; 'Automotive'